2017
DOI: 10.1027/0227-5910/a000413
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perspectives on the Stigma of Suicide Attempt Survivors

Abstract: Participants experienced public stigma, self-stigma, and label avoidance. Analyses reveal that the stigma of suicide shares similarities with stereotypes of mental illness, but also includes some important differences. Attempt survivors may be subject to double stigma, which impedes recovery and access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 37 publications
6
70
1
1
Order By: Relevance
“…However, it is unclear whether this same effect occurs when the information is collected via other means, such as a face‐to‐face interview. Pervasive stigma regarding suicidal behavior (Frey, Hans, & Cerel, ; Sheehan, Corrigan, & Al‐Khouja, ) likely plays a role in individuals’ concealment of their intentions regarding their recent or current behavior. This stigma could also lead family members to participate in concealment of suicidal intent.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether this same effect occurs when the information is collected via other means, such as a face‐to‐face interview. Pervasive stigma regarding suicidal behavior (Frey, Hans, & Cerel, ; Sheehan, Corrigan, & Al‐Khouja, ) likely plays a role in individuals’ concealment of their intentions regarding their recent or current behavior. This stigma could also lead family members to participate in concealment of suicidal intent.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive documentation in the literature of stigma toward individuals with a history of suicidal ideation and suicidal behavior (Batterham, Calear, & Christensen, ; Tadros & Jolley, ). People who struggle with suicidality have been labeled by the general public as attention‐seeking, weak, and cowardly (Sheehan, Corrigan, Al‐Khouja, & the Stigma of Suicide Research Team, ; Sudak, Maxim, & Carpenter, ). Despite the intuitive view that health care workers are more compassionate and understanding toward individuals experiencing suicidality, such professionals are not immune to endorsing stigmatizing attitudes (Gillig, Hillard, Deddens, Bell, & Combs, ; Norheim, Grimholt, & Ekeberg, ).…”
Section: Obstacles To Service Provisionmentioning
confidence: 99%
“…In order to avoid stigmatization, it is probable that suicidal individuals choose not to communicate warning signs. In fact, suicide attempt survivors experience self-stigma in addition to stigma from others (Sheehan, Corrigan, & Al-Khouja, 2016). In one study, an attempter believed he was "weak" and another thought "something was wrong with him" (Sheehan et al, 2016).…”
mentioning
confidence: 99%
“…In fact, suicide attempt survivors experience self-stigma in addition to stigma from others (Sheehan, Corrigan, & Al-Khouja, 2016). In one study, an attempter believed he was "weak" and another thought "something was wrong with him" (Sheehan et al, 2016). Sheehan et al (2016) also found non-fatal suicide attempters were commonly seen as attention-seeking, selfish, incompetent, emotionally weak, and immoral.…”
mentioning
confidence: 99%
See 1 more Smart Citation